BAITUL MAAL PROSPERITY IN CIVIC ECONOMY AS A MANIFESTATION OF THE VOLUNTARISM FORMATION IN KASIH SAYANG VILLAGE LANGKAT REGENCY - Junaidi, Junaidi; Jamaludin, Jamaludin; Hodriani, Hodriani; Laila, Hapni; Ivanna, Julia; Madiyoh, Abdulhakim (Al-Qalam, 2024)
This research aims to examine the concept of Baitul Maal in realizing prosperity in Kasih Sayang Village, which is based on Islamic principles and Pancasila values to foster a civic economy approach in daily life. The study also explores how the community of Kasih Sayang Village cultivates a sense of citizenship through voluntarism that contributes to social harmony and well-being. The research utilized a qualitative method with a phenomenological approach. Data collection techniques were observation, interviews, and documentation. The analysis employed interpretative phenomenological analysis with the assistance of the ATLAS.ti software for ease and innovation in research data analysis. Research findings reveal that Baitul Maal in Kasih Sayang Village serves as an economic center and an economicdesign reflecting unity, collaboration, development, and empowerment. The role of Baitul Maal extends beyond economic aspects. It integrates Pancasila values, citizenship spirit, and sustainability to propel the community toward holistic development and empowerment. The community of Kasih Sayang Village is grounded in three voluntarism concepts: teodical (reliance on God), ethical (contributing based on goodwill), and psychological (internal drive). Integrating these concepts creates a harmonious environment in the village, where spiritual, moral, and psychological values unite to achieve shared prosperity.